EGOIN theory and its implications to the development in central China - Cheng, Fusheng (2008)
Seek out how to continue the rise of the middle plain areas of inland China by combining the analysis of standardization and reality, the study of theories and analysis of real-life problems as well as nation-wide research and international comparison. An analysis on the development of Henan Province will also be done and suggestions will be provided to serve as an example.